2012
DOI: 10.4321/s1130-01082012000800004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between insufflation with air or carbon dioxide during the colonoscopy in sedated patients with propofol

Abstract: Objectives: compare the intensity of pain experienced after colonoscopy with air or with CO 2 and evaluate the safety of CO 2 in colonoscopies performed with moderate/deep sedation.Materials and methods: individuals undergoing ambulatory colonoscopy without exclusion criteria (severe respiratory disease, morbid obesity) were randomized in air or CO 2 group. We recorded different variables prior to, during and upon completion of the colonoscopy, performing monitoring using pulse oximetry and capnography. Each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
(35 reference statements)
1
9
0
1
Order By: Relevance
“…. Twenty‐one RCTs on 3607 patients were retrieved from the electronic databases. There were 1801 patients in the CI group and 1806 in the AI group (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Twenty‐one RCTs on 3607 patients were retrieved from the electronic databases. There were 1801 patients in the CI group and 1806 in the AI group (Table ).…”
Section: Resultsmentioning
confidence: 99%
“… reported the combined analysis of nine RCTs in two separate studies and concluded that CI could decrease abdominal discomfort during and following colonoscopy without any additional adverse reaction, warranting its routine clinical use. The RCTs included in the present review evaluated procedure‐related pain either as a primary or secondary outcome according to the trial protocol; this variable is a major source of morbidity and influences the quality of life in patients undergoing colonoscopy. It was thoroughly investigated in the included RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported on the frequency of PCO 2 values that exceeded 55 mm Hg. 25,28,30 Two of the studies showed comparable incidences, whereas the third found that 16% of patients undergoing CO 2 insufflation had transient PCO 2 values >55 mm Hg compared with none in the room-air insufflation group. End tidal CO 2 was assessed in 6 studies, 13,17,21,28,41,44 with 3 studies indicating a significantly higher value in the CO 2 insufflation groups, either during or at the end of the procedures, whereas 3 studies reported no difference.…”
Section: Safetymentioning
confidence: 99%
“…Twenty-five of 36 of the studies discussed in this review reported no serious adverse events or untoward outcomes related to the use of CO 2 as an insufflation agent. Only 2 studies reported on significant respiratory events, with 1 showing no difference in rates of respiratory depression or apnea (air 3.5%, CO 2 3.9%) 30 and another indicating reversible respiratory depression in 2 patients undergoing ERCP with air insufflation. 25 There has been some concern regarding the use of CO 2 as an insufflation agent in patients with chronic obstructive pulmonary disease because this patient group may have an increased risk of CO 2 retention.…”
Section: Safetymentioning
confidence: 99%
“…In this sense, performing the procedure with the patient in the prone position may be a non-invasive way to increase oxygenation in patients with acute respiratory distress [26]. While patients with morbid obesity have been excluded from most studies evaluating carbon dioxide (CO 2 ) insufflation in colonoscopy, those obese patients with a BMI \ 40 kg/m 2 have not; thus, a recent study did not report higher levels of end-tidal CO 2 or adverse respiratory events in morbidly obese subjects [27].…”
mentioning
confidence: 99%